MO448MICRORNAS IMPLICATED IN CHRONIC KIDNEY DISEASE. (29th May 2021) - Metzinger, Laurent
Abstract: Background and Aims: The gene program is controlled at the post-transcriptional level by the action of small non-coding RNAs known as microRNAs (miRNAs), short, single-stranded molecules that control mRNA stability or translational repression via base pairing with regions in the 3' untranslated region of their target mRNAs. Recently, considerable progress has been made to elucidate the roles of miRNAs in vascular pathogenesis and develop the use of miRNAs as biomarkers, and innovative drugs. We demonstrated during the last decade that miRNAs miR-126 and miR-223 are implicated in the course of chronic kidney disease (CKD) and cardiovascular damage. miR-223 expression is enhanced in vascular smooth muscle cells (VSMCs) subjected to an uremic toxin and also in aortas of a murine model of CKD. As restenosis is a common complication of angioplasty, in which neointimal hyperplasia results from migration of VSMCs into the vessel lumen we measured the effect of miR-223 modulation on restenosis in a rat model of carotid artery after balloon injury. We over-expressed and inhibited miR-223 expression using adenoviral vectors, coding a pre-miR-223 sequence or a sponge sequence, used to trap endogenous microRNA, respectively. We demonstrated that inhibiting miR-223 function significantly reduced neointimal hyperplasia by almost half in carotids. Thus down-regulating miR-223 could be a potential therapeutic approach to prevent restenosis after angioplasty. We also correlated miR-126 and miR-223 expression with clinical outcomes in a large cohort of CKD patients, in collaboration with the University Hospital of Ghent (Belgium) and Ambroise Paré Hospital, France. We evaluated both miRNA's link with all-cause mortality and cardiovascular and renal events over a 6-year follow-up period. The serum levels of miR-126 and miR-223 were decreased as CKD stage advanced, and patients with higher levels of miR-126 and miR-223 had a higher survival rate. Similar results were observed for cardiovascular and renal events. In conclusion, CKD is associated with a decrease in circulating miR-126 and miR-223 levels in CKD patients. We will also present links between several uremic toxin concentrations and miRNA concentration in the patients of this cohort. Finally, anemia is a common feature of CKD that is associated with cardiovascular disease and poor clinical outcomes. A mixture of uremic toxins accumulates in the blood of CKD patients during the course of the disease, and there is good evidence that they modulate erythropoiesis, explaining at least partly anemia. The exact molecular mechanisms implicated are however poorly understood, although recent progresses have been made to identify key components in the CKD process. We will present results on the effect of uremic toxins on erythropoiesis, having an impact on cell metabolism during this process. Taken together, our findings could be of interest to both researchers and clinicians working in the field since they might shed new light on the molecular mechanisms involved in the CKD process. MicroRNAs implicated in Chronic Kidney Disease Pr. Laurent Metzinger, UR-UPJV 4666 HEMATIM, CURS, Université de Picardie Jules Verne, CHU Amiens Sud, Avenue René Laënnec, Salouel, F-80054, Amiens, France. Tel: (+33) 22 82 53 56, Email: laurent.metzinger@u-picardie.fr